In Vitro Antibacterial Activities of JNJ-Q2, a New Broad-Spectrum Fluoroquinolone - Morrow, Brian J. (American Society for Microbiology (ASM), 2010)
JNJ-Q2, a novel fluorinated 4-quinolone, was evaluated for its antibacterial potency by broth and agar microdilution MIC methods in studies focused on skin and respiratory tract pathogens, including strains exhibiting contemporary fluoroquinolone resistance phenotypes. Against a set of 118 recent clinical isolates of Streptococcus pneumoniae, including fluoroquinolone-resistant variants bearing multiple DNA topoisomerase target mutations, an MIC(90) value for JNJ-Q2 of 0.12 μg/ml was determined, indicating that it was 32-fold more potent than moxifloxacin. Against a collection of 345 recently collected methicillin-resistant Staphylococcus aureus (MRSA) isolates, including 256 ciprofloxacin-resistant strains, the JNJ-Q2 MIC(90) value was 0.25 μg/ml, similarly indicating that it was 32-fold more potent than moxifloxacin. The activities of JNJ-Q2 against Gram-negative pathogens were generally comparable to those of moxifloxacin. In further studies, JNJ-Q2 exhibited bactericidal activities at 2× and 4× MIC levels against clinical isolates of S. pneumoniae and MRSA with various fluoroquinolone susceptibilities, and its activities were enhanced over those of moxifloxacin. In these studies, the activity exhibited against strains bearing gyrA, parC, or gyrA plus parC mutations was indicative of the relatively balanced (equipotent) activity of JNJ-Q2 against the DNA topoisomerase target enzymes. Finally, determination of the relative rates or frequencies of the spontaneous development of resistance to JNJ-Q2 at 2× and 4× MICs in S. pneumoniae, MRSA, and Escherichia coli were indicative of a lower potential for resistance development than that for current fluoroquinolones. In conclusion, JNJ-Q2 exhibits a range of antibacterial activities in vitro that is supportive of its further evaluation as a potential new agent for the treatment of skin and respiratory tract infections.